AB0468 Channeling of Biologic Agents: Comparing Baseline Characteristics of Biologic Naïve Rheumatoid Arthritis Patients Initiating Abatacept, as Compared to Other Biologic Agents and Small Molecule Agents. (9th June 2015) - Harrold, L.R.; Gandhi, K.K.; Etzel, C.J.; Nadkarni, A.; Saunders, K.C.; Kelly, S.; Kremer, J.M.
Abstract : Background: There is limited evidence comparing the types of patients initiated on different classes of biologic medications, and this information is critical when conducting comparative observational research among patients with RA. Objectives: This study compared baseline characteristics of biologic naïve rheumatoid arthritis (RA) patients initiating abatacept as compared to tumor necrosis factor inhibitors (TNFi), and other non-TNFi biologics and small molecules (non-TNFi/sm). Methods: Biologics naïve RA patients who initiated abatacept, TNFi and other non-TNFi/sm from 12/2005 to 8/2014 within the Corrona registry were identified. Initiation of first biologic or small molecule (first line use) was defined as first indication of biologic use for a patient that was previously naïve to any biologic or small molecule prior to initiation of study drug. Baseline characteristics at time of biologic initiation were captured including demographics, comorbid conditions, and RA disease characteristics including age at disease onset, disease duration, prior and concomitant medication use, and disease activity. Descriptive statistics were performed including t-tests and Chi-square tests comparing abatacept initiators to TNFi and other non-TNFi/sm initiators. Results: Among the 4, 232 first time biologic users, 364 (9%) initiated abatacept, 3689 (87%) TNFi, and 179 (4%) other non-TNFi/sm. Abatacept initiators as compared to TNFi initiators were more likely to be older (62.8 years (yrs) vs 56 yrs; P<0.001), female (81% vs 75%; P=0.039), with a lower mean BMI (28.8 vs 29.9; P=0.007). In terms of RA characteristics, the abatacept initiators had older age at disease onset, greater disease duration, and were more likely to be unemployed or disabled (Table 1 ) as compared to the TNFi initiators. They also more frequently had prior and concomitant use of non-MTX nonbiologic disease modifying anti-rheumatic drugs (nbDMARDs), and lower doses of concomitant prednisone as compared to TNFi prednisone users. Similarly abatacept initiators as compared to non-TNFi/sm initiators were more likely to be older (62.8 yrs vs 60 yrs; P=0.025) at time of biologic/small molecule initiation. With regard to RA characteristics, abatacept initiators as compared to non-TNFi/sm initiators were more likely to have an older age of RA onset, more often on concomitant MTX and non-MTX nbDMARDs. Conclusions: In a real world national cohort of biologic naïve RA patients, those initiated on abatacept had a different profile than those initiating TNFi and non-TNFi/sm. Specifically abatacept users were older at the time of biologic/small molecule initiation, had onset of RA at an older age, and were more frequently using concomitant non-MTX nbDMARDS. Additionally abatacept initiators had a longer disease duration as compared to TNFi initiators. These findings are consistent with data from real-world registries in the US and Europe. Acknowledgements: This study is sponsored by Corrona, LLC. The Corrona RA registry has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, Astra Zeneca, BMS, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, and UCB. Disclosure of Interest: L. Harrold Grant/research support from: Corrona, LLC., K. Gandhi Employee of: Bristol-Myers Squibb, C. Etzel Employee of: Corrona, LLC., A. Nadkarni Employee of: Bristol-Myers Squibb, K. Saunders Employee of: Corrona, LLC., S. Kelly Employee of: Bristol-Myers Squibb, J. Kremer Shareholder of: Corrona, LLC., Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, LLC.